IDENTIFYING THE CRIME OF INSIDER TRADING FERIENJOB IN GERMANY AND LEGAL PROTECTION FOR INDONESIAN STUDENTS - Anjani, Alia Savitri; Jannah, Putri Wardatul; Kusumaningtyas, Yara; Rahayu, Winda; Albariansnyah, Hamonangan (Sriwijaya Crimen and Legal Studies, 2024)
The phenomenon of ferienjob (seasonal work) in Germany is increasingly attractive to international students, including those from Indonesia, as it offers income opportunities and work experience abroad. However, behind the legality and attractiveness of this work, some loopholes can be used for exploitation, which in some instances can lead to the crime of trafficking in persons. This study aims to identify modes of exploitation in the context of ferienjob and evaluate the level of legal protection available to Indonesian students, both from German and Indonesian law perspectives. The study reveals the existence of covert forced labor practices, violations of labor rights, and a lack of supervision of employment agencies facilitating Indonesian students. In addition, the different legal regimes in the two countries often cause uncertainty regarding legal protection, mainly when violations occur outside the home country's jurisdiction. The results show that despite applicable legal instruments, the implementation of protection for Indonesian students working in Germany still needs to be improved.